Pengaruh Penerapan LKPD Berbasis PjBL Terhadap Kemampuan Berpikir Kreatif Peserta Didik Pada Pembelajaran PAI - Rezkia Zanianti, Mifa; Kasja Eki Waluyo; Tajudin Nur (Universitas Majalengka, 2024)
The purpose of this study is to see if there is an influence between PjBL-based LKPD on students' creative thinking skills in PAI learning. The research method used is a quantitative experiment of the pseudo-experiment type with a non-equivalent group design which contains pretest, posttest, and two treatments. The results of the tests carried out in this study are descriptive analysis, normality test, homogeneity test and hypothesis test with paired sample t-test type. Based on the results of the study, it can be seen that in the descriptive analysis between the experimental class there is an increase of 38.63 while the control class is 36.42, in the normality test of the experimental class and the control class can be said to be distributed normally because the data produced > 0.05, in the homogeneity test of the pretest based on mean of 0.690 and the posstest of 0.690, it can be concluded that it is homogeneous, In the hypothesis test of the value of Sig. 0.0000 < 0.05, Therefore, it can be concluded that it is homogeneous, in the hypothesis test of the Sig value. 0.0000 < 0.05, it can be concluded that there is an influence of PjBL-based LKPD on students' ability in PAI learning.